TQM’s Theory - Belkasseh, Mohammed (Archives of Business Research, 2019)
This paper suggests a literature review attempting to an in-depth look to the scientific thought around quality implementation in organizations. It provides a critical view to the plethora of designations mentioned in many contributions that are not necessarily different in their respective meanings. This would disperse the concentration and slow down the pace of quality theory’s scientific evolution. The paper joins a set of contributions to suggest TQM as a unifying concept that would enable to overcome the delay of recognition of quality implementation as a theory.